2019
DOI: 10.1155/2019/1376515
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Appendage Occlusion Guided Only by Transesophageal Echocardiography

Abstract: Aims To investigate a new method of left atrial appendage occlusion without fluoroscopy. Methods and Results We performed left atrial appendage occlusion for 14 patients with atrial fibrillation in our hospital. All of the surgeries were completed in a general surgery setting, avoiding fluoroscopy, and in each case, the entire procedure was guided by transesophageal echocardiography (TEE). All of the surgeries were performed through the femoral vein pathway. All operations went smoothly with no serious complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…[ 29 ] Incomplete blockade (shunt >5 mm) can still lead to cardiogenic thrombosis, and oral anticoagulation will still be a daily task for these patients. [ 30 ] To address these issues, some scholars have proposed Three/3 Dimensions modeling of the LAA opening and then Three/3 Dimensions printing to guide LAAO, [ 31 ] while some scholars [ 32 ] have proposed multi-angle and multi-dimensional occlusion guidance to achieve the best fit of the occluder disk to the LAA opening. However, we believe that, in addition to the above methods, upgrading the blocking device, customizing the blocker according to the anatomical structure of the patient’s LAA and the opening, or adopting an umbrella-type structure for the external disk to cover as wide a range of LAA openings as possible may be a direction or trend for future research.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] Incomplete blockade (shunt >5 mm) can still lead to cardiogenic thrombosis, and oral anticoagulation will still be a daily task for these patients. [ 30 ] To address these issues, some scholars have proposed Three/3 Dimensions modeling of the LAA opening and then Three/3 Dimensions printing to guide LAAO, [ 31 ] while some scholars [ 32 ] have proposed multi-angle and multi-dimensional occlusion guidance to achieve the best fit of the occluder disk to the LAA opening. However, we believe that, in addition to the above methods, upgrading the blocking device, customizing the blocker according to the anatomical structure of the patient’s LAA and the opening, or adopting an umbrella-type structure for the external disk to cover as wide a range of LAA openings as possible may be a direction or trend for future research.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data on LAA occlusion guided solely by TEE. A single-center prospective study with 14 patients demonstrated successful and safe implantation of LAmbre (LAA occlusion device; Lifetech Scientific (Shenzhen) Co. Ltd., Shenzhen, China) with TEE only [4].…”
Section: Discussionmentioning
confidence: 99%
“…In order to make full use of the advantages of TEE, we have been able to complete percutaneous endocardial LAA occlusion under the guidance of TEE alone, avoiding the radiation of doctors and patients (18). In the cases of thoracoscopic radiofrequency ablation, we also performed percutaneous LAA occlusion guided by TEE.…”
Section: Discussionmentioning
confidence: 99%